An investigation into linguistic features of directives in school announcements in english - Lê, Hồng Dương (ĐHĐN., 2015)
This thesis examined the linguistic features of directives in school announcements. The directives investigated in this study is identified as a type of speech acts used in school announcements aims at the fact that they are attempts by the addresser as school management/director board to get the addressees as students/teachers to do something expressed by the propositional content. This study was conducted with qualitative and descriptive methods. Over two hundred English samples of school announcements were collected from the official Websites of high schools and universities in Britain, the U.S and English speaking countries. The study found that in aspect of syntax, the sentences used in school announcements appeared in such sentence types as: imperatives, declaratives and interrogatives. In the aspect of pragmatics, the result of data analysis revealed the qualitative information about the speech acts in the functions of school announcements as the sub-types of directives, namely inviting, suggesting, advising and requesting. The result of the investigation is expected to help learners of English understand the linguistic features of directives in school announcements and then help them have a new look in preparing an announcement of their own in English.